Receptor dependent 3D-QSAR study of P. falciparum Plasmepsin II inhibitors - Silva, Rita Yanka Pereira da (2019)
Malaria represents an actual scenario of importance for Drug Discovery. Plasmodium falciparum, the most virulent form of the parasite, is responsible for increasing resistance to current therapy. In this context, Plasmepsin II represents a potential pharmaceutical target for malaria inhibition. It’s a protein part of a group of aspartic proteases responsible for Plasmodium's metabolism of hemoglobin. Two series of inhibitors were used to creat two predictive LQTA-3D-QSAR models. The molecules binding model was estimated by means of molecular dynamics simulations, when necessary. The models performed really well for an external dataset. Activity cliff profile was obtained by comparing all molecules via Tanimoto similarity. The cliffs were depicted using Gephi software. The models were used to predict the activity of plasmepsin II inhibitors.